ASPECTS OF BREEDING IN VNIISSOK OF GREEN PEA FOR CANNING - E. P. Pronina; I. P. Kotlyar; I. M. Kaygorodova; V. A. Ushakov (Овощи России, 2015)
The article presents the methods and results of the competitive breeding of promising high-quality varieties of vegetable green pea for canning, as well as the main achievements of FGBNU VNIISSOK.